2012
DOI: 10.1017/s1368980011003612
|View full text |Cite
|
Sign up to set email alerts
|

Differences in vitamin D status and calcium metabolism in Saudi Arabian boys and girls aged 6 to 18 years: effects of age, gender, extent of veiling and physical activity with concomitant implications for bone health

Abstract: Objective: Few data exist looking at vitamin D status and bone health in schoolaged boys and girls from Saudi Arabia. The present study aimed to determine the extent of poor vitamin D status in school boys and girls aged 6-18 years and to examine if there was any difference in status with age, physical activity and veiling and concomitant effects on bone. Design: Cross-sectional study. Setting: Jeddah, Kingdom of Saudi Arabia. Subjects: A total of 150 boys (7-16 years) and 150 girls (6-18 years) from local sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
6
20
0
2
Order By: Relevance
“…Limited studies available on prevalence of child malnutrition from KSA suggest national data may alone be misleading in understanding the determinants and consequences and stoutly emphasize that it is crucial to focus on regional inequality which can be a result of ethnic as well as environmental conditions [10, 12, 19]. Few available studies documented the existence of prevalence of deficiencies of micronutrients like vitamin A, vitamin D, calcium, iron, iodine, and zinc among children of KSA (all mentioned nutrients known to influence growth and development of children) and also emphasized the need for higher number of studies to understand the wider impact of these deficiencies [22–25]. …”
Section: Resultsmentioning
confidence: 99%
“…Limited studies available on prevalence of child malnutrition from KSA suggest national data may alone be misleading in understanding the determinants and consequences and stoutly emphasize that it is crucial to focus on regional inequality which can be a result of ethnic as well as environmental conditions [10, 12, 19]. Few available studies documented the existence of prevalence of deficiencies of micronutrients like vitamin A, vitamin D, calcium, iron, iodine, and zinc among children of KSA (all mentioned nutrients known to influence growth and development of children) and also emphasized the need for higher number of studies to understand the wider impact of these deficiencies [22–25]. …”
Section: Resultsmentioning
confidence: 99%
“…Evidence suggests that 25(OH) D blood levels should be maintained above 20 ng/ml to prevent rickets and osteomalacia 16 . However, levels should be above 30 ng/ml to maximize vitamin D's effect on calcium, bone and muscle metabolism 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, clothing style may not be a major predictor of vitamin D deficiency levels under low ambient UVB level conditions. Saudi Arabian researchers have also found that vitamin D levels can be affected by clothing styles (24) . Pregnant women in their third trimester exhibited lower vitamin D levels than women in their first trimester of gestation (16·2 v. 17·0 ng/ml, P = 0·0243) in our study.…”
Section: Discussionmentioning
confidence: 99%